2021
DOI: 10.3390/jrfm14080356
|View full text |Cite
|
Sign up to set email alerts
|

Cash Holding and Firm Value in the Presence of Managerial Optimism

Abstract: Cash holding is important for Chinese manufacturing firms coping with the increasing costs of financing and tough economic conditions. This study examines the impact of cash holding on the firm value of Chinese manufacturing businesses. We found evidence that a non-linear relationship exists between cash holding and firm value in these companies. The study reveals that a higher level of cash holding in financially constrained firms negatively affects the firm value, while unconstrained firms with a less cash h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
(116 reference statements)
4
9
1
Order By: Relevance
“…However, the results of this study are not in line with Habib et al (2021), who proved that cash holding has a negative effect on firm value in a constrained firm, Ameer (2012) discovered that cash holdings negatively affect the firm value for closely held firms., which explained that Cash Holding does not affect the value company. This is due to the level of cash availability owned and controlled by financial managers because companies tend to use cash to meet all needs.…”
Section: The Role Of Cash Holding On Firm Valuecontrasting
confidence: 91%
See 1 more Smart Citation
“…However, the results of this study are not in line with Habib et al (2021), who proved that cash holding has a negative effect on firm value in a constrained firm, Ameer (2012) discovered that cash holdings negatively affect the firm value for closely held firms., which explained that Cash Holding does not affect the value company. This is due to the level of cash availability owned and controlled by financial managers because companies tend to use cash to meet all needs.…”
Section: The Role Of Cash Holding On Firm Valuecontrasting
confidence: 91%
“…The first hypothesis was accepted or proven so changes in the increase or decrease in cash holdings are able to affect the value of a company. These results are in line with Habib et al (2021) proved that cash holding positively affects firm value in an unconstrained firm. Ameer (2012), Minh HA &Minh TAİ (2017), andChandra &Feliana (2020) also found that cash holding positively affects firm value.…”
Section: The Role Of Cash Holding On Firm Valuesupporting
confidence: 91%
“…Previous studies have demonstrated that a conflict of interest negatively affects the price share and high levels of cash holding may result in being exposed to agency problems through a manager's exploitation of cash resources to achieve personal benefits at the expense of negative reflection on stock returns, which results in higher agency costs and lower investment efficiency, and then a negative reflection on stock returns (Ferreira & Vilela, 2004;Mun et al, 2020;Habib et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, cash holdings can help avoid financial distress in difficult times. Cash reserves help firms cope with higher costs of financing, or economic hardship (Habib et al 2021). Thus, retaining cash can act as a precaution (Boot, Vladimirov 2019).…”
Section: The Effect Of Cash Holdings On Financial Performancementioning
confidence: 99%